Estabilidad de Taludes del Tajo Abierto Jésica considerando el Macizo Rocoso Isotrópico y Anisotrópico - Herrera Carranza, Editta (2020)
The research paper analyzes the stability of the global slope, in six types of hydrothermal alteration present in the open pit Jésica, identifies the isotropic rock mass, that is, it does not have preferential orientation of discontinuities and anisotropic taking into account the parallel or sub-parallel discontinuities to the slope. For the slope stability analysis of the isotropic and anisotropic rock mass, the Generalized Hoek-Brown and Generalized Anisotropic failure criteria were used respectively, both in Slide 6.0 software. Two sets of discontinuities sub-parallel to the slope were considered in the anisotropic stability analysis F1 (dip from 72° to 82°) y F2 (dip from 45° to 55°). The safety factors obtained considering the anisotropic rock mass are up to 29% lower than those obtained in the isotropic rock mass; as well as the higher quality of the rock mass, the greater the variation of the safety factors, this difference is more marked in the sulphides zone with the set F2, where in a rock mass with RMR 40 the safety factor decreases by 8%, while in a rock mass with RMR 61 the safety factor decreases by 29%.